2016
DOI: 10.3917/cips.111.0305
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes des étudiants hétérosexuels envers le mariage des personnes de même sexe et l’homoparentalité en France

Abstract: Distribution électronique Cairn.info pour Presses universitaires de Liège. © Presses universitaires de Liège. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
1
1
4
Order By: Relevance
“…In summary, the results show that despite negative attitudes towards marriage and adoption by homosexuals, positive attitudes predominated, unlike previous studies that identified a predominance of opposing attitudes (Scherman et al, 2020;Tomczak & Zawadzka-Witt , 2021;Gato & Fontaine, 2016), including from people with religious beliefs (Gross et al, 2018;Lee & Multz, 2019;Vecho et al, 2016;Whitehead & Perry, 2016).…”
Section: Final Considerationscontrasting
confidence: 94%
See 1 more Smart Citation
“…In summary, the results show that despite negative attitudes towards marriage and adoption by homosexuals, positive attitudes predominated, unlike previous studies that identified a predominance of opposing attitudes (Scherman et al, 2020;Tomczak & Zawadzka-Witt , 2021;Gato & Fontaine, 2016), including from people with religious beliefs (Gross et al, 2018;Lee & Multz, 2019;Vecho et al, 2016;Whitehead & Perry, 2016).…”
Section: Final Considerationscontrasting
confidence: 94%
“…Gross et al (2018), for example, found that in a sample of French heterosexual students, Catholic participants were less favorable to homoparenthood than those without religious affiliations, and the level of religiosity intensifies this rejection. In another French study, the results showed that religiosity plays a moderating role in the association between attitudes and political orientation and sexual prejudice (Vecho et al, 2016). Whitehead and Perry (2016), in turn, demonstrated that religious factors, such as attendance at religious services and reading of sacred texts, are among the strongest predictors of opposition to adoption by same-sex couples.…”
Section: Attitudes About Rights To Civil Marriage and Adoption By Lgbsmentioning
confidence: 93%
“…De façon similaire, les réponses aux questions sur les droits et sur l'adoption montrent le fort impact des changements législatifs québécois et canadiens en matière de filiation et de mariage pour les couples de même sexe survenus au cours des années 2000 (Bureau, 2009;Tremblay, 2015). Souvent considérées comme le dernier bastion d'homophobie, les réactions négatives à l'égard des familles homoparentales tendent à s'amenuiser dès lors que la reconnaissance juridique est atteinte et que des modèles familiaux de parents LGB s'ajoutent aux représentations sociales du couple et de la famille (Vecho, Gross, Gratton, D'Amore et Green, 2016). Ces résultats sont aussi congruents avec ceux d'une analyse de la composition du bassin de bénévoles du GRIS-Montréal effectuée précédemment ayant montré une augmentation importante du nombre de parents LGB entre la fin des années 1990, époque à laquelle le GRIS ne comptait aucun parent dans ses rangs, et aujourd'hui où plusieurs dizaines d'entre eux présentent leur vécu parental lors des interventions du GRIS (Vallerand et al, 2017, p. 127).…”
Section: Discussionunclassified
“…Os resultados demonstraram a diferenciação do posicionamento entre pessoas conservadoras e liberais. A homofobia associa-se ao perfil conservador, em que as atitudes negativas confirmam suas ideologias acerca da formação familiar e adoção, o foco principal é a manutenção à noção de família tradicional (Vecho et al, 2016). O perfil liberal apresenta fundamento em estudos de psicologia e medicina, o que todavia é fruto de permissividade a compreensão de assuntos emergentes na sociedade (Ferraz, 2015;Gomes, & Serôdio, 2014).…”
Section: Discussionunclassified